Une analyse discursive de l’acte humoristique à travers les créations lexicales dans la presse francophone algérienne - Samira Allam Iddou (Multilinguales)
Our contribution aims to highlight the humorous act in French-speaking journalistic discourse through lexical creations. While lexical innovation has been the subject of much study, we haven’t found any studies devoted to the humorous neology of the French-speaking Algerian press. To this end, we allow ourselves to update a discursive analysis of humor through the lexical creations manifest in journalistic discourse. In the framework of this study, we first propose to identify all the creations that can serve as a basis for humorous effects in order to analyze them, then we highlight the implementation of the lexical creation process.